Tamanho dos clubes, funções de congestionamento e economias de escala na provisão de bens públicos locais no Brasil - Silva, Laércio Damiane Cerqueira da (2015)
The thesis studies, in three chapters, on the provision of public goods in municipalities. The first chapter puts in competition two alternative specifications, one on the demand side and another on the supply side, to a set of 5285 municipalities data for 2010 in order to test the hypothesis that the relevance of the models that explain the behavior local government spending can depend on the size of the population of the jurisdictions. The econometric methodology uses a combination of Test J proposed by Davidson and MacKinnon (1981), with the threshold suggested by Hansen (2000), as a data screening method to test whether the response of local governments to their constituents is stable between small and large municipalities. Results show that the median voter model applies to smaller cities, with great population size ranging between 13604 and 13661 inhabitants, depending on the congestion function used. Nevertheless, it rejected in 2293 municipalities, for which the model-oriented supply fits better. In the second chapter, these alternative models of determination of public provision in order to measure the impact of the size of cities on the quality of public services applies - via analysis of advertising and rivalry of goods - in 5268 Brazilian municipalities based on the Theory of Clubs. For both models, the results point to the existence of spatial correlation between municipalities, suggesting that spending patterns in a given locality influence on the fiscal decisions of neighbors. Proves the hypothesis that the size of the clubs, and the cost of utilities differentiate the results of the provision of action, supporting the literature on the subject which argues that in smaller jurisdictions proximity of voters with its public officials exerts more pressure and control over their political acts, and that aggregate individual preferences have less heterogeneity and can represent the community as a whole. This result yields a larger congestion effect to the larger cities, which goes against the international literature. Finally, using a set of data that make up Brazilian localities Public Consortia Inter-municipal public services, the third chapter aims to establish empirical evidence for a phenomenon called by Oates (1988) as "zoo-effect." According to this effect, the lowest level of expenditure in smaller towns should not be explained by the smaller clusters, but simply by the fact that certain categories of spending - like a zoo - they need a minimum population size to be provided. Thus, the positive relationship between population size and local spending on public services does not take into account the fact that in the most populous cities, the basket of services offered is broader and more diverse, and for this reason, estimates of existing congestion tend to be overestimated. By spatial statistics confirmed the hypothesis of the zoo effect on municipalities, and that the more diversified the range of services expands the range of services in neighboring areas, which explains the interaction between the municipalities as a way to get better and higher level of public services to its citizens. Evidence shows that the intensity of the effect depends on the urban-rural gradient, with the biggest phenomenon in urban areas due to more substantial economies of scale in these locations.